ANALYSIS OF THE FACTORS AFFECTING MEASUREMENT AND ACCOUNTING DISCLOSURE FOR HUMAN RESOURCE AND THEIR IMPACT ON THE QUALITY OF FINANCIAL REPORTS IN IRAQI BANKS - Thaar Umran Mousa; Noor Nadhim Hameed AL-Jassam; Allawi Shahad Dahham (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2022)
The research aims to explore the impact of factors related to some of the characteristics of the bank, which are size, age, nature of activity, profitability and nationality in the measurement and accounting disclosure of HRin the annual financial reports of banks, in addition to showing their impact on the quality of financial reports, and the following main hypothesis has been put forward: (It can be determined The factors that affect the measurement and accounting disclosure for HRthat affect the quality of financial reports), and these factors were determined by the size of the bank, the age, nature of its activity, profitability and nationality. The research sample is represented by a group of managers and heads of the departments of management and financial departments in Iraqi banks for the data for the fiscal year ending on December 31, 2019. The content is to identify the HR related paragraphs that have already been disclosed in these reports. A multiple regression model was also applied to test the research hypotheses. The results indicated that the level of public disclosure of HR in the annual financial reports was average, and that there was a significant effect of the bank’s characteristics of size, age, profitability, and nationality on the level of this disclosure of HRin those reports.